Deteksi Kerusakan Pipa Dalam Bentuk Sumbat Dan Bocor Menggunakan Sinyal Suara Dan Empat Mikrofon - Willy Hartino Siregar; Feblil Huda; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The system piping is a system that is used to distribute the fluid in the form of a substance of liquid or gas from one point to multiple points more to distance the relatively long. By because it’s, various types of damage that can occur in the system piping becomes important to be studied and prevented. Prevention of damage, be it leaks or blockages, is very important because it can reduce the number of losses both to the economy, the natural environment, and even loss of life. In this study, a method was developed to detect damage to pipes using sound signals. The detection of damage to the plumbing done by using a signal sounds and four microphones. Methods of signal noise is a smart structural health monitoring that can detect damage at the cost of the more inexpensive. Excitation noise is given by using a loudspeaker and the response signal noise is sampled using four microphones that are connected to the PC- Oscilloscope which serves to convert the signal analog results of recording sound into a signal of digital form of the value of domains of time and then use a Continuous Wavelet Transform (CWT) to determine the location of the damage that occurs in the pipe sheath. To detect the location of pipe damage in various positions of damage, it can be searched by comparing the wavelet coefficient of the four microphones. Keywords: sound signal, leakage, blockage, Continous Wavelet Transform, wavelet coefficient